2018
DOI: 10.1101/281451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of buspirone on the H-reflex in acute spinal decerebrated mice

Abstract: 2 KEY POINTS SUMMARY Buspirone, a partial serotoninergic agonist (5HT1A), exerts a considerable acute facilitation of spinally-mediated locomotion after a complete spinal lesion in mice.  Since locomotion is associated with reflex modulation, we focused in this study on the effect of buspirone on H-reflex in acute spinal mice after decerebration and removal of anesthesia.  Buspirone injection resulted in a depression of the H-reflex during the first 20 minutes followed, 40 minutes later, by an increase of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Since buspirone had no effect if preceded by NAD-299, it is suggested that reflex modulation by buspirone is mediated by 5-HT 1A receptors. Some of these results have been presented in abstract form Develle and Leblond (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since buspirone had no effect if preceded by NAD-299, it is suggested that reflex modulation by buspirone is mediated by 5-HT 1A receptors. Some of these results have been presented in abstract form Develle and Leblond (2016).…”
Section: Introductionmentioning
confidence: 99%